2009
DOI: 10.1002/ajim.20772
|View full text |Cite
|
Sign up to set email alerts
|

Occupational injuries among emergency responders

Abstract: The physical demands of emergency response are a leading cause of injuries that may benefit from similar interventions across the occupations. To assess risk, improved exposure data need to be acquired, particularly for volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
144
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(161 citation statements)
references
References 10 publications
14
144
0
3
Order By: Relevance
“…First, large standard errors associated with the small sample sizes restrict detailed reporting of injury characteristics (Reichard & Jackson, 2010). Second, the national estimates reported in this study are probably underestimates due to the difficulty in case identification of correctional officers with certainty.…”
Section: Discussionmentioning
confidence: 81%
“…First, large standard errors associated with the small sample sizes restrict detailed reporting of injury characteristics (Reichard & Jackson, 2010). Second, the national estimates reported in this study are probably underestimates due to the difficulty in case identification of correctional officers with certainty.…”
Section: Discussionmentioning
confidence: 81%
“…The coding of occupation has many unique features compared to coding other types of open responses: coders must assign a description to one of hundreds of possible codes rather than just a handful, the open answers are short and factual rather than long and attitudinal, and occupation coders who make this their profession become very skilled. The data about occupation that are produced through the coding process are commonly used to study various phenomena occurring in the labor force, including sex segregation (Anker 1998), work-related injuries (Cawley and Homce 2003;Layne 2004;Reichard and Jackson 2010), health-related exposures (Kromhout et al 1993;Hammond et al 1995;Kauppinen et al 2000), wage inequality (Lettau 2003;Heywood and O'Halloran 2005;Bjerk 2007), mobility (Shniper 2005;Moscarini and Thomsson 2007), and occupational projections (Rosenthal 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Being a police officer is recognized as a dangerous occupation [1][2][3]. An American study has found a much higher occupational fatality rate in police officers when compared with the national average [4].…”
Section: Introductionmentioning
confidence: 99%